1984
DOI: 10.1177/32.12.6150057
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic and GABAergic anatomical relationship in the rat substantia nigra, locus coeruleus, and hypothalamic median eminence: immunocytochemical visualization of biosynthetic enzymes on serial semithin plastic-embedded sections.

Abstract: The visualization of protein antigens has been performed on semithin sections embedded in Araldite. After partial removal of the resin and a light proteolytic treatment of the tissue we were able to localize several biosynthetic enzymes: tyrosine hydroxylase (TH), phenylethanolamine N-methyltransferase (PNMT), and glutamic acid decarboxylase (GAD), which are, respectively, markers of catecholaminergic, adrenergic, gamma-aminobutyric acid (GABA)ergic systems. This technique afforded a high resolution of light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Localization of GABAergic neurons within the peri-LC dendritic field (Ijima and Ohtomo, 1988;Jones, 1991) also raises the possibility that interneurons in this region contribute to the functional modulation of LC activity. This possibility is supported by the demonstration that the LC is densely innervated by GABA fibers (Berod et al, 1984;Mugnaini and Oertel, 1985;Ennis and Aston-Jones, 1989;Aston-Jones et al, 1991). Collectively, these observations suggest that GABA input to LC neurons from these local neurons in the peri-LC zone might constitute a previously unrecognized interneuronal pool for the LC.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Localization of GABAergic neurons within the peri-LC dendritic field (Ijima and Ohtomo, 1988;Jones, 1991) also raises the possibility that interneurons in this region contribute to the functional modulation of LC activity. This possibility is supported by the demonstration that the LC is densely innervated by GABA fibers (Berod et al, 1984;Mugnaini and Oertel, 1985;Ennis and Aston-Jones, 1989;Aston-Jones et al, 1991). Collectively, these observations suggest that GABA input to LC neurons from these local neurons in the peri-LC zone might constitute a previously unrecognized interneuronal pool for the LC.…”
Section: Introductionsupporting
confidence: 68%
“…Tissue was incubated overnight in a sheep anti-GAD antibody (1:2000; gift from M. L. Tappaz, Lyon, France) in PBS (without Triton X-100 to reveal fibers) at room temperature. Specificity of the antiserum for GAD has been established in previous studies (Oertel et al, 1982;Berod et al, 1984). For bright-field staining, after incubation in the primary antibody sections were incubated in a biotinylated donkey anti-sheep IgG (1:500; The Jackson Laboratory) in PBS for 90 min at room temperature followed by ABC Elite reagents (1:1000; Vector Laboratories, Burlingame, CA) diluted in PBS for 90 min at room temperature.…”
Section: Perfusion and Tissue Processingmentioning
confidence: 99%
“…There are apparently no GABA cell bodies intrinsic to the LC, but glutamic acid decarboxylase immunoreactive nerve terminals are present, closely juxtaposed to noradrenergic cell bodies and dendrites [6]. GABA inhibits the firing of LC neurons primarily by activation of GABA A receptors [44], but compared to other brain regions, the human LC has a low density of GABA A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter part of the results has not been reported to our knowledge. Significantly smaller size of GABAergic neurons compared with that of surrounding noradrenergic neurons, together with the paucity of GABAergic cells in the LC, makes it difficult to recognize them in abundant GABAergic neuropil encircling these noradrenergic neurons in Vibratome sections of the LC with GABA-and GAD-antisera (3,23,24). We obtained positive results with the PAP method on 4 ~Cm serial paraffin sections of the whole LC, and by discriminating between GABAergic intrinsc and perinuclear neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known of the GABAergic inhibition on the activity of these noradrenergic neurons of the LC. Although some authors (3,23,24) limited GABA-like immunoreactive (GABA-LI) elements to the abundant neuropil encircling these neurons, recent immunocytochemical studies demonstrated GABA-LI in a few small and medium-sized intrinsic neurons of the rat LC on Vibratome and paraffin sections (13,14). Some authors reported the heterogeneity of the LC concerning neurochemical architecture by detecting serotonin Although Olschowka et al (22) studied noradrenergic synapses in the rat brain electron microscopically by dopamine-jS-hydroxylase immunocytochemistry , the ratio of GABAergic synapses to aminergic ones in the LC has not been reported .…”
mentioning
confidence: 99%